Social anxiety and eating disorder comorbidity: The role of negative social evaluation fears - Levinson, Cheri A. (2011)
Social anxiety and eating disorders are highly comorbid. However, it is unknown how specific domains of social anxiety relate to disordered eating. We provide data on these relationships and investigate social appearance anxiety and fear of negative evaluation as potential vulnerabilities linking social anxiety with eating disorders. Specifically, we examined five domains of social anxiety: Social interaction anxiety, fear of scrutiny, fear of positive evaluation, fear of negative evaluation, and social appearance anxiety. Results indicated that social appearance anxiety predicted body dissatisfaction, bulimia symptoms, shape concern, weight concern, and eating concern over and above fear of scrutiny, social interaction anxiety, and fear of positive evaluation. Fear of negative evaluation uniquely predicted drive for thinness and restraint. Structural equation modeling supported a model in which social appearance anxiety and fear of negative evaluation are vulnerabilities for both social anxiety and eating disorder symptoms. Interventions that target these negative social evaluation fears may help prevent development of eating disorders.